A novel frameshift mutation in ubiquitin-specific protease 26 gene in a patient with severe oligozoospermia. Issue 4 (23rd April 2020) - Li, Leilei; Xi, Qi; Zhang, Hongguo; Fei, Jia; Jiang, Yuting; Li, Linlin; Liu, Ruizhi; Wang, Ruixue; Zhang, Guirong
Abstract: Ubiquitin-specific protease 26 ( USP26 ) encodes a predicted protein containing his- and cys- domains that are conserved among deubiquitinating enzymes. USP26 is specifically expressed in testis tissue and is a potential infertility gene. In the present study, we performed genetic testing related to spermatogenesis impairment in a patient with idiopathic severe oligozoospermia to identify the cause. The patient underwent clinical examination and reproductive hormone testing. Genes associated with male infertility, including USP26, were assessed by targeted exome sequencing. A novel frameshift mutation, c.2195delT (p.Phe732Serfs*14), was identified in USP26 . This frameshift mutation was located in residue 732 of USP26 gene, leading to loss of the conserved deubiquitinating enzyme His-domain and producing a truncated protein of 744 amino acids. Bioinformatics analysis revealed this mutation to be pathogenic. A novel framshift mutation c.2195delT (p.Phe732Serfs*14) in USP26 gene was reported to be associated with male infertility in a Chinese patient with severe oligozoospermia.